Tissue factor and factor VII: initiation of blood coagulation - McVey, John (Henry Stewart Talks, 2007)
Tissue factor and factor VII, Initiation of blood coagulation, Vertebrate blood coagulation, The resting state, The procoagulant response, The anticoagulant response, Molecular pathology, Tissue factor, Factor VII, Tissue factor pathway inhibitor
Reviewed at 2015/12/15